Potential programming of dopaminergic circuits by early life stress - Rodrigues, Ana João (2011)
Stress and high levels of glucocorticoids during pre- and early postnatal life seem to alter developmental programs that assure dopaminergic transmission in the mesolimbic, mesocortical and nigrostriatal systems. The induced changes are likely to be determined by the ontogenetic state of development of these brain regions at the time of stress exposure and their stability is associated with increased lifetime susceptibility to psychiatric disorders, including drug addiction. This article is intended to serve as a starting point for future studies aimed at the attenuation or reversal of the effects of adverse early life events on dopamine-regulated behaviors.